Model Kepatuhan Pajak UMKM Berbasis Literasi Pajak, Etika Sosial, Kepercayaan Publik, dan Budaya Kalosara - Abdul Rachman Rika (JURNAL AKUNTANSI BARELANG, 2026)
This study investigates the impact of tax literacy and social ethics on MSME tax compliance in Kendari City, with public trust as a mediating variable and Kalosara as a moderating cultural factor. Kalosara, a traditional value system of the Tolaki ethnic group, emphasizes justice and harmony, making it potentially influential in tax behavior. The study used a quantitative method with 150 MSME respondents and employed Structural Equation Modeling with SmartPLS. The results indicate that social ethics significantly influence tax compliance, both directly and indirectly through public trust. Tax literacy, however, does not directly influence compliance but shows a significant indirect effect through trust. Kalosara strengthens the effect of social ethics on tax compliance. The model explains 63.4% of the variance in tax compliance (R² = 0.634). Theoretically, the study extends the Theory of Planned Behavior by incorporating public trust and indigenous cultural values (Kalosara) as behavioral determinants. Practically, the findings inform tax authorities on the importance of culturally embedded strategies to foster voluntary compliance among MSMEs.